ممارسة مهنة المراجعة الخارجية في الجزائر في ظل تبني المعايير الدولية للمراجعة ومدى جاهزية البيئة للتطبيق - بوقرن, دليلة; شعباني, لطفي (جامعة الوادي University of Eloued, 2021)
تهدف هذه الدراسة إلى معرفة واقع ممارسة مهنة المراجعة الخارجية في الجزائر خاصة بعد الإصلاحات التي مست المهنة وصدور القانون 10-01، كما تسعى أيضا إلى إلقاء الضوء على معايير المراجعة الجزائرية التي أصدرها المجلس الوطني للمحاسبة منذ سنة 2016، ولتحقيق أهداف الدراسة واختبار الفرضيات تم إعداد استبيان لعينة من الأكاديميين والمهنيين يتضمن مجموعة من الأسئلة تعالج موضوع الدراسة. توصلت الدراسة أن هناك تطور وتحسن في ممارسة مهنة المراجعة الخارجية في الجزائر بعد صدور القانون 10-01 ، وأن المعايير الجزائرية للمراجعة تتماشى وتلائم البيئة الاقتصادية الجزائرية، كما أن هناك توافق بين المعايير الجزائرية للمراجعة والمعايير الدولية للمراجعة. The aim of this study is to learn the reality of the practice of external auditing in Algeria ,especially after the reforms that affected the profession and the promulgation of Act 10-01, It also seeks to highlight the Algerian auditing standards issued by the National Accounting Council since 2016 ,In order to achieve the objectives of the study and test hypotheses ,a questionnaire was prepared for a sample of academics and professionals ,including a set of questions on the subject of the study. The study found that there has been an improvement in the practice of external audits in Algeria following the promulgation of the 10-01 Act ,that the Algerian criteria for auditing are in compliance with the Algerian economic environment ,the Algerian standards of audits are also compatible with International standards of the audits.
The practice of external auditing in Algeria with the adoption of international auditing standards and the readiness of the environment for application
مقال
Keywords: المراجعة الخارجية، المعايير الدولية للمراجعة، المعايير الجزائرية للمراجعة.